Who owns the land? Perspectives from rural Ugandans and implications for land acquisitions - Bomuhangi, Allan; Doss, Cheryl; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2011)
Rapid growth of demand for agricultural land is putting pressure on property rights systems, particularly in Sub-Saharan Africa, where customary tenure systems have provided secure land access. Patterns of gradual, endogenous change toward formalization are being challenged by rapid and large-scale demands from outsiders. Little attention has focused on the gender dimensions of this transformation. Based on a study of land tenure in Uganda, this paper analyzes how different ways of defining landownership—based on household reports, existence of ownership documents, and rights over the land—provide very different indications of the gendered patterns of landownership and rights. Although many households report that husbands and wives jointly own the land, women are less likely to be listed on ownership documents, especially titles, and women have fewer land rights. A simplistic focus on title to land misses much of the reality regarding land tenure and could especially have an adverse impact on women's land rights.